Severo Sarduy and the neo-baroque image of thought in the visual arts - Perez, Rolando (Purdue studies in Romance literatures, 2012)
"Severo Sarduy never enjoyed the same level of notoriety as did other Latin American writers. On the other hand, he never lacked for excellent critical interpretations of his work from critics like Roberto González Echevarría, René Prieto, Gustavo Guerrero, and other reputable scholars. Missing, however, from what is otherwise an impressive body of critical commentary, is a study of the importance of painting and architecture, first, to his theory, and second, to his creative work. In order to fill this lacuna in Sarduy studies, Rolando Pérez's book undertakes a critical approach to Sarduy's essays--"Barroco, Escrito sobre un cuerpo," "Barroco y neobarroco," and "La simulación"--The stand point of art history. In short, no book on Sarduy until now has traced the multifaceted art historical background that informed the work of this challenging and exciting writer. It will be a book that many a critic of Sarduy and the Latin American "baroque" will consult in years to come"--